Relaying of Maize With Potato Under Maize-Fallow-T. Aman Cropping Pattern in Charland (Bangladesh Journal of Agricultural Research, 2023)
A field experiment was conducted in the charland of the Jamuna river under Sundargonj upazilla (AEZ 3) of Gaibandha during 2017-18 and 2018-19. Two cropping systems were compared: Potato/Maize-T. Aman (relay cropping of maize with potato) and Maize-Fallow-T. Aman. The experiment was laidout in six dispersed replications maintaining randomized complete block design (RCB) design. The results revealed that the improved cropping pattern (Potato/Maize- T. Aman) produced the higher system rice equivalent yield (21.58 t ha-1) than the existing cropping pattern (11.61 t ha-1), that is almost double than the existing cropping pattern. Similarly, the production efficiency (PE) was 44% higher in the improved cropping pattern with a value of 70 kg ha-1 day-1 than the existing ones (48.5 kg ha-1 day-1). The land use efficiency (LUE) was also 29% more in the same cropping pattern (84.5%) compared to the farmers existing cropping pattern (65.5%). The profitability in terms of gross margin was almost double in the improved cropping pattern (Tk. 1,95,630) than the farmers’ existing cropping pattern (Tk. 1,00,750). Inclusion of Potato relay with the existing cropping increase the system productivity and MBCR (1.91) of the farmers in the char areas.Bangladesh J. Agril. Res. 46(1): 99-106, March 2021